The role of architecture in the shaping of livable territories and futures - Velazco López, René (2023)
Faced with the socio-environmental challenges present today and those looming in the future, systemic and transversal criteria are presented from which architecture as a discipline can take a determining role and being part of a comprehensive response with the purpose to form socioecological systems that allow the search and obtaining of well-being.